THE INFLUENCE OF TRUST AND COMMITMENT ON SUPPLY CHAIN PERFORMANCE MEDIATED BY INFORMATION SHARING - Syahrul Muhaji; Moh Mukhsin; Diqbal Satyanegara (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The purpose of this study was to determine the effects of trust, commitment, and information sharing on supply chain performance. This research uses quantitative methods and employs saturated sampling techniques by distributing questionnaires to 36 respondents. The results indicated that trust has a positive but insignificant effect on supply chain performance, while both commitment and information sharing have positive and significant effects on supply chain performance. Additionally, trust positively and significantly affects information sharing, as does commitment. Furthermore, information sharing effectively mediates the relationship between trust and commitment in relation to supply chain performance. The adjusted R-squared value is 0.747, concluding that trust, commitment, and information sharing affect supply chain performance by 74.7%, with the remaining 25.3% influenced by other variables outside this study. Keywords: Trust; Commitment; Information Sharing; Supply Chain Performance